Electronic public procurement in Bangladesh: Bangladesh priorities - Abdallah, Wahid (BRAC Institute of Governance and Development (BIGD), 2022)
An efficient public procurement system in a country is essential for effectual public investment and economic growth. However, in developing countries like Bangladesh, public procurement is plagued with various inefficient practices. An ongoing project that started in 2008 aims to reform public procurement in Bangladesh. By 2011, four Bangladeshi agencies had implemented electronic procurement, representing about 10% of all public procurement. If anyone can easily bid on a government contract from their office or even own home, and if everyone feels that the process will be fair, more companies are likely to bid. More bids for a given project increases competition, leading to lower prices tendered to the government. The research analyzes data from the Local Government Engineering Department (LGED), which implemented e-GP in 2011. LGED first introduced e-GP as a very small pilot in 2012. After great expansion, about 95% of LGED procurement uses e-GP today. This paper attempts to conduct a cost-benefit analysis of this e-GP initiative. The paper found multiple benefits of e-GP. Firstly, since participation is online, any registered user with internet can apply. Also, as bidders can participate from home or office removing the necessity to visit the procuring entity’s office, the collusive elite-bidder groups cannot block non-collusive bidders anymore from participating in the bidding process, resulting in greater competition and thus lower prices for publicly procured goods, works, and services. The benefit of e-GP stems from the removal of artificial market distortions. On the other hand, there will be operational and maintenance costs as well as that of training the public officials who will run it. Hence, this cost estimation will be based on project documents and discussions with relevant officials.